Administrative Enforcement of Food Safety Regulation in Indonesia: Loopholes and Recommendations - Stephanie Apsari Putri (LAW REFORM, 2022)
Food safety regulation requires adequate resources. Due to its complexity, food safety regulation needs multidisciplinary stakeholder intervention. The National Agency for Drug and Food Control (NADFC) as the appointed body encountered problems in law enforcement works with other food safety-related bodies. The discussion focuses on the administrative enforcement of food safety regulation in Indonesia and these shortcomings is followed with analysis of some possible solutions. However, their performances are hampered by several issues. This research is conducted with a desktop study of information obtained from primary and secondary sources. Also, to get some insights to improve the administrative enforcement in Indonesia, this study is carried out using comparative method. Therefore, the New South Wales (NSW) laws, regulations, policies, and principles are analysed. This study finds that the drawbacks of the administrative enforcement of food safety regulation in Indonesia is caused by limited enforcement funding; lack of community knowledge and awareness towards food safety; lack of competent food inspectors; and lack of coordination between food safety administrative bodies. Some recommendations have been proposed, namely applying industry funding; implementing food hygiene rating; establishing enforcement guidelines; and appointing a single coordinating body for food safety.